Expectant long‐term follow‐up of patients with chronic urinary retention. Issue 1 (8th November 2018) - Abello, Alejandro; DeWolf, William C.; Das, Anurag K.
Abstract : Aims: To describe urologic complications in patients with chronically elevated post‐void residual (PVR) volumes and to evaluate other related risk factors during a long‐term follow‐up in patients managed conservatively. Methods: Non‐neurogenic patients who refused surgical intervention of the prostate and had PVR volumes >300 mL on two or more separate occasions at least 6 months apart were included. We followed this cohort over time, recorded complications and evaluated risk factors for complications. Results: Twenty‐eight men with a mean age of 74 were followed for a median of 56 months (IQR: 26‐101 months); 26 had benign prostatic hyperplasia with a median prostate size of 55 cc. Baseline median PVR was 468 cc (IQR: 395‐828) and follow‐up median PVR was 508 cc (IQR: 322‐714). During follow‐up, 13 patients (46%) had at least one complication with acute urinary retention being the most common occurring in 10 patients (36%) with 15 episodes. Other complications presented in less than 15%, and no patients developed permanent renal insufficiency. Patients with prostate size ≥ 100 cc had significantly higher total number of acute retention episodes ( P ‐value: 0.01). Conclusions: Although the presence of CUR could commonly predispose to episodes of acute retention, severe complications are infrequent although present. Additionally, prostate size may play a role in increasing some adverse outcomes. With proper counseling about different complications, patients with retention who denied surgical treatment can be safely followed for at least 5 years without renal deterioration.